2008
DOI: 10.1103/physrevlett.100.123001
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine-Structure-Induced Purely Long-Range Molecules

Abstract: We have experimentally observed and theoretically identified a novel class of purely long-range molecules. This novel purely long-range state is formed due to a very weak hyperfine interaction that is usually treated only as a small perturbation in molecular spectra. Photoassociation spectroscopy of ultracold ytterbium (171Yb) atoms with the 1S0-3P1 intercombination transition presents clear identification of molecular states and the shallowest molecular potential depth of about 750 MHz among the purely long-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…When the spectrum is dominated by the features due to the ground state d-wave, the intensity ratio of the J e = 3 and J e = 1 features should be 3/2 from Eq. (14). Such d-wave doublets in 174 Yb were observed by Tojo et al [13], who found that the transition to the bound state with J e = 3 can be stronger than the transition to J e = 1 at relatively low collisions energies corresponding to a temperature of about 25 µK, what can be explained by our model.…”
Section: Isotopic Variation Of Photoassociation Spectrasupporting
confidence: 64%
See 2 more Smart Citations
“…When the spectrum is dominated by the features due to the ground state d-wave, the intensity ratio of the J e = 3 and J e = 1 features should be 3/2 from Eq. (14). Such d-wave doublets in 174 Yb were observed by Tojo et al [13], who found that the transition to the bound state with J e = 3 can be stronger than the transition to J e = 1 at relatively low collisions energies corresponding to a temperature of about 25 µK, what can be explained by our model.…”
Section: Isotopic Variation Of Photoassociation Spectrasupporting
confidence: 64%
“…Our models of the interaction potentials can be used to predict the magnitude of the optical lengths in Eq. (6) for the set of optical Feshbach resonances corresponding to the photoassociation lines of the different Yb bosonic isotopes (fermionic isotopes are more complicated because of hyperfine structure in the excited state [14]). Figure 7 shows our calculated optical lengths for the homonuclear bosonic isotopes of Yb.…”
Section: Isotopic Variation Of Photoassociation Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The upper binding potential supports as many as 8 bound states. Without cavity coupling the binding energies match well with the reported free space values [36]. We have found that with strong coupling they do not change appreciably.…”
Section: Resultssupporting
confidence: 87%
“…[52] and C 6 = 2810 a.u. [36] for molecular potentials asymptotically corresponding to 1 S 0 + Figure 4. Asymptote potentials of one-photon (i) and two-photon (ii) sector.…”
Section: Resultsmentioning
confidence: 99%